The cluster approach as an effective tool for the development of the tourism potential of smaller towns - O. V. Gorbunova (Вестник университета)
The possibility for the development of the tourism potential of smaller towns through interregional cooperation has been considered. The importance of clusters and the interaction between organizations through networking has been substantiated. It has been noted, that the clusters constitute the main approach for the implementation of the tourism strategy in the Russian Federation. The Southern Tourist Cluster of the Moscow Region has been currently developed, has been reviewed. The main goals of the cluster and the tourism potential of the residential areas included in the cluster has been analyzed. Two types of tourism as the ones with greatest potential: cultural-historical and gastronomical have been substantiated. It has been concluded, that the consolidation of the tourism potential of smaller residential areas, and the creation of clusters, plays an important role in the development of tourism in the Russian Federation and the improvement of the competitiveness of the national tourist product.